Biogeochemical cycling in the Bering Sea over the onset of major Northern Hemisphere Glaciation. (17th September 2016) - Swann, George E. A.; Snelling, Andrea M.; Pike, Jennifer
Abstract: The Bering Sea is one of the most biologically productive regions in the marine system and plays a key role in regulating the flow of waters to the Arctic Ocean and into the subarctic North Pacific Ocean. Cores from Integrated Ocean Drilling Program (IODP) Expedition 323 to the Bering Sea provide the first opportunity to obtain reconstructions from the region that extend back to the Pliocene. Previous research at Bowers Ridge, south Bering Sea, has revealed stable levels of siliceous productivity over the onset of major Northern Hemisphere Glaciation (NHG) (circa 2.85–2.73 Ma). However, diatom silica isotope records of oxygen (δ 18 Odiatom ) and silicon (δ 30 Sidiatom ) presented here demonstrate that this interval was associated with a progressive increase in the supply of silicic acid to the region, superimposed on shift to a more dynamic environment characterized by colder temperatures and increased sea ice. This concluded at 2.58 Ma with a sharp increase in diatom productivity, further increases in photic zone nutrient availability and a permanent shift to colder sea surface conditions. These transitions are suggested to reflect a gradually more intense nutrient leakage from the subarctic northwest Pacific Ocean, with increases in productivity further aided by increased sea ice‐ and wind‐driven mixing in the Bering Sea. In suggesting a linkage in biogeochemical cycling between the south Bering Sea and subarctic Northwest Pacific Ocean, mainly via the Kamchatka Strait, this work highlights the need to consider the interconnectivity of these two systems when future reconstructions are carried out in the region. Key Points: Nutrient leakage from the subarctic North Pacific Ocean to Bering Sea from 2.73 Ma Abrupt increase in silicic acid supply at 2.58 Ma increases siliceous productivity in the Bering Sea Bering Sea productivity increase at 2.58 Ma is concordant with shift to permanently colder conditions